2022
DOI: 10.1136/bmjgh-2021-006583
|View full text |Cite
|
Sign up to set email alerts
|

Examining the substance use, violence, and HIV and AIDS (SAVA) syndemic among urban refugee youth in Kampala, Uganda: cross-sectional survey findings

Abstract: BackgroundInteractions between substance use, violence, HIV and AIDS, known as the ‘SAVA’ syndemic, are understudied among refugee youth. We assessed the synergistic effects of frequent alcohol use, depression and violence on HIV vulnerability among urban refugee youth aged 16–24 years in Kampala, Uganda.MethodsWe conducted a cross-sectional survey between January and April 2018 with a convenience sample of refugee youth aged 16–24 years living in informal settlements in Kampala (Kabalagala, Rubaga, Kansanga, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…Generally, there was a lot of diversity in the way violence was conceptualised and measured. Hadush et al [ 86 ], Logie et al [ 88 ], Ogbonnaya et al [ 72 ], Okenwa-Emegwa et al [ 73 ], Segneri [ 90 ], Stewart et al [ 78 ] and Zadnik et al [ 82 ] all adopted a validated tool to measure violence (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, there was a lot of diversity in the way violence was conceptualised and measured. Hadush et al [ 86 ], Logie et al [ 88 ], Ogbonnaya et al [ 72 ], Okenwa-Emegwa et al [ 73 ], Segneri [ 90 ], Stewart et al [ 78 ] and Zadnik et al [ 82 ] all adopted a validated tool to measure violence (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We collected data on violence occurring in 44 different countries, grouped by region: Europe [ 22 , 62 , 65 , 68 , 81 , 91 ]; North America [ 64 , 67 , 69 , 72 , 74 , 75 , 78 , 80 , 82 , 85 ]; Asia [ 31 , 76 , 87 ]; and Africa [ 70 , 71 , 77 , 84 , 86 , 88 ]. Twenty-five of the included reports measured violence in a single country [ 64 , 65 , 67 , 69 , 70 72 , 74 , 75 , 77 , 78 , 81 , 82 , 84 89 , 91 , 93 , 94 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with the existing literature (36,37) that has found that continuous exposure to traumatic events is associated with alcohol use. Additionally, researchers (35,(43)(44)(45) have illuminated that refugees who experience war or conflict-related trauma are at greater risk for poor mental health and alcohol abuse. This study has revealed that some youth consume alcohol to cope with and forget war-related atrocities.…”
Section: Discussionmentioning
confidence: 99%